A miniaturized push–pull-perfusion probe for few-second sampling of neurotransmitters in the mouse brain. Issue 8 (14th March 2019) - van den Brink, Floris T. G.; Phisonkunkasem, Thas; Asthana, Ashish; Bomer, Johan G.; van den Maagdenberg, Arn M. J. M.; Tolner, Else A.; Odijk, Mathieu
Abstract : Measuring neurotransmitters in the brain of living animals is a challenging task, especially when detailed information at high temporal resolution is required. Abstract : Measuring biomolecule concentrations in the brain of living animals, in real time, is a challenging task, especially when detailed information at high temporal resolution is also required. Traditionally, microdialysis probes are used that generally have sampling areas in the order of about 1 mm 2, and provide information on concentrations with a temporal resolution of at least several minutes. In this paper, we present a novel miniaturized push–pull perfusion sampling probe that uses an array of small 3 μm-wide sampling channels to sample neurotransmitters at a typical recovery rate of 61%, with a reduced risk of clogging. The added feature to segment the dialysate inside the probe into small water-in-decane droplets enables the detection of concentrations with a temporal resolution of a few seconds. Here we used the probe for in vivo recordings of neurotransmitter glutamate released upon electrical stimulation in the brain of a mouse to demonstrate the feasibility of the probe for real-time neurochemical brain analysis.